DYSLIPIDEMIA IN PATIENTS WITH RHEUMATOID ARTHRITIS DEPENDS ON COMORBID PATHOLOGY AND GENETIC PREDICTORS - Bukach, O.P.; Buzdugan, I.O. (World of Medicine and Biology, 2022)
The purpose of the study was to investigate the dynamics of the blood lipid spectrum under the influence of treatment depending on comorbid pathology and polymorphism of the gene T-786C endothelial nitric oxide synthase in patients with rheumatoid arthritis. 110 patients with rheumatoid arthritis and 20 practically healthy people were examined and treated. In the study, the concentration of high-density lipoprotein cholesterol decreased in patients with rheumatoid arthritis – by 22.3 %, rheumatoid arthritis, arterial hypertension – by 29.27 %, rheumatoid arthritis, arterial hypertension, abdominal obesity – by 33.61 %, rheumatoid arthritis, arterial hypertension, abdominal obesity, type 2 diabetes mellitus – by 44.55 %. The increase in total cholesterol, low-density lipoprotein cholesterol and triglycerides depending on the gene polymorphism is found in 87.5 %, 62.5 %, 100 % of patients with CC genotype, in 56.52 %, 47.83 %, 78.26 % of patients with TC genotype, 56.52 %, 37.93 % and in 75.86 % of patients with TT genotype. A comprehensive treatment of rheumatoid arthritis with comorbid pathology was proposed by adding telmisartan, rosuvastatin and L-arginine to the basic therapy.